Iron‐based coupling media for MRI‐guided ultrasound surgery. Issue 12 (7th November 2022) - Allen, Steven P.; Fergusson, Austin; Edsall, Connor; Chen, Sheng; Moore, David; Vlaisavljevich, Eli; Davis, Richey M.; Meyer, Craig H.
Abstract: Purpose: In this study, we examine the effects of a recently developed, iron‐based coupling medium (IBCM) on guidance magnetic resonance (MR) scans during transcranial, magnetic‐resonance‐guided, focused ultrasound surgery (tMRgFUS) procedures. More specifically, this study tests the hypotheses that the use of the IBCM will (a) not adversely affect image quality, (b) remove aliasing from small field‐of‐view scans, and (c) decouple image quality from the motion state of the coupling fluid. Methods: An IBCM, whose chemical synthesis and characterization are reported elsewhere, was used as a coupling medium during tMRgFUS procedures on gel phantoms. Guidance magnetization‐prepared rapid‐gradient‐echo (MP‐RAGE), TSE, and GRE scans were acquired with fields of view of 28 and 18 cm. Experiments were repeated with the IBCM in several distinct flow states. GRE scans were used to estimate temperature time courses as a gel target was insonated. IBCM performance was measured by computing (i) the root mean square difference (RMSD) of TSE and GRE pixel values acquired using water and the IBCM, relative to the use of water; (ii) through‐time temperature uncertainty for GRE scans; and (iii) Bland–Altman analysis of the temperature time courses. Finally, guidance TSE and GRE scans of a human volunteer were acquired during a separate sham tMRgFUS procedure. As a control, all experiments were repeated using a water coupling medium. Results: Use of the IBCM reduced RMSD in TSE scans by a factor of 4 or more for all fields of view and nonstationary motion states, but did not reduce RMSD estimates in MP‐RAGE scans. With the coupling media in a stationary state, the IBCM altered estimates of temperature uncertainty relative to the use of water by less than 0.2°C. However, with a high flow state, the IBCM reduced temperature uncertainties by the statistically significant amounts (at the 0.01 level) of 0.5°C (28 cm field of view) and 5°C (18 cm field of view). Bland–Altman analyses found a 0.1°C ± 0.5°C difference between temperature estimates acquired using water and the IBCM as coupling media. Finally, scans of a human volunteer using the IBCM indicate more conspicuous grey/white matter contrast, a reduction in aliasing, and a less than 0.2°C change in temperature uncertainty. Conclusions: The use of an IBCM during tMRgFUS procedures does not adversely affect image quality for TSE and GRE scans, can decouple image quality from the motion state of the coupling fluid, and can remove aliasing from scans where the field of view is set to be much smaller than the spatial extent of the coupling fluid.